Neonatal Intensive Care Unit Nurses Working in an Open Ward: Stress and Work Satisfaction. Issue 3 (July 2016) - Lavoie-Tremblay, Mélanie; Feeley, Nancy; Lavigne, Geneviève L.; Genest, Christine; Robins, Stéphanie; Fréchette, Julie
Abstract : There is some research on the impact of open-ward unit design on the health of babies and the stress experienced by parents and nurses in neonatal intensive care units. However, few studies have explored the factors associated with nurse stress and work satisfaction among nurses practicing in open-ward neonatal intensive care units. The purpose of this study was to examine what factors are associated with nurse stress and work satisfaction among nurses practicing in an open-ward neonatal intensive care unit. A cross-sectional correlational design was used in this study. Participants were nurses employed in a 34-bed open-ward neonatal intensive care unit in a major university-affiliated hospital in Montréal, Quebec, Canada. A total of 94 nurses were eligible, and 86 completed questionnaires (91% response rate). Descriptive statistics were computed to describe the participants' characteristics. To identify factors associated with nurse stress and work satisfaction, correlational analysis and multiple regression analyses were performed with the Nurse Stress Scale and the Global Work Satisfaction scores as the dependent variables. Different factors predict neonatal intensive care unit nurses' stress and job satisfaction, including support, family-centered care, performance obstacles, work schedule, education, and employment status. In order to provide neonatal intensive care units nurses with a supportive environment, managers can provide direct social support to nurses and influence the culture around teamwork.